The Return of the Original Phillips curve? An Assessment of Lars E. O. Svensson's Critique of the Riksbank's Inflation Targeting, 1997-2012 - Fredrik N. G. Andersson; Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2015)
We assess Lars E O Svensson's prominent critique of the Swedish Riksbank. We reject his two major claims: first that the Riksbank has anchored inflation expectations at the 2 percent inflation target, and second, that the original version of the Phillips curve, based constant inflation expectations, is appropriate to calculate the unemployment effects of monetary policy. We find his conclusion that the Riksbank's policy has contributed to an average of 38 000 more unemployed every year 1997-2011 misleading. We also show that the inflation targeting of the Riksbank 1995-2014 is successful compared to previous monetary regimes.
Keywords: D84; E24; E31; E52; E58; 330; Sweden; inflation targeting; Phillips curve; inflation expectations; Swedish Riksbank; unemployment